The ProStart school-to-work program: a follow-up study to assess student outcomes - Koessl, Deena S., author; Albright, Leonard, advisor; Nelson, Barbara J., committee member; Morgan, George A., committee member; Smith, Ken, committee member (Colorado State University. Libraries, 2005)
Since the ProStart school-to-work program began in the mid-1990s, there has been speculation about the post-secondary outcomes of its graduates. Knowing what ProStart graduates do after high school graduation, specifically if they stay in the industry either through education or employment, is important to stakeholders. Further, knowing which aspects of students' high school education are associated with matriculation to college and the workplace has implications for future program improvements. In addition to its use here, the methodology employed in this study should be of assistance to other professionals involved in similar career-oriented high school programs. Student reported data from recent graduates was used to track their postsecondary education and employment paths; this information was obtained through individual telephone interviews with 100 students. The Colorado Restaurant Association Education Fund (CRAEF) supplied additional data about student engagement while in school. The information was then analyzed to determine significant relationships. The results of this study showed that 68% of former ProStart students were attending college. Further, 27% of the total were attending a post-secondary institution and majoring in an industry-related field (18%) or business (9%); another 11% of the total planned to attend college and major in an industry-related field (8%) or business (3%). In addition, 42% of the total worked in an industry-related occupation; another 9% were seeking employment in the industry. There were several factors that seemed to influence ProStart students' matriculation into post-secondary educational environments. First, student engagement in all program components was associated with favorable ProStart high school outcomes. Second, the highly engaged students who received financial post-secondary support were more likely to have favorable outcomes—they were more likely to attend college, have a higher GPA, and be majoring or planning to major in an industry-related field. There were several factors that seemed to influence ProStart students' matriculation into the industry. Again, student engagement in most of the program components was associated with favorable ProStart high school outcomes. Further, receiving the National Certificate as a result of being highly engaged was important; students who received the National Certificate were more likely to work in the industry post-secondarily.
Keywords: vocational education